A nação diáspórica japonesa em Brazi-Maru, de Karen Tei Yamashita - Otenio, Marta Matsue Yamamoto [UNESP]; Rapucci, Cleide Antonia [UNESP] (My University, 2013)
From a reading of the novel Brazil-Maru by Karen Tei Yamashita, this article focuses mainly on discussing about Japanese colonies’formation in Brazil, as well as the reasons that stimulated Japanese immigrants to invest their efforts in the process of this new undertaking. Some peculiarities between nucleous in the countryside of the state of São Paulo and Esperança’s community formation of this novel will be discussed and compared in the present work. The theoretical supports about the concept of Nation by Ernest Renan and the concept of Imagined Communities by Benedict Anderson compose the theoretical basis for understanding the constitution of Japanese diasporic nation in Brazil.

A partir de uma leitura do romance Brazil-Maru, de Karen Tei Yamashita, este artigo tem como foco principal discutir a formação das colônias japonesas no Brasil, bem como os motivos que levaram os imigrantes japoneses a investirem seus esforços no processo desse novo empreendimento. Algumas peculiaridades entre núcleos do interior paulista e a formação da comunidade Esperança do romance serão abordadas e confrontadas no presente trabalho. Os suportes teóricos sobre o conceito de Nação, de Ernest Renan, e as Comunidades Imaginadas de Benedict Anderson, constituem a base teórica para compreendermos a constituição da nação diaspórica japonesa no Brasil.
The Japanese diasporic nation in Brazil-Maru, by Karen Tei Yamashita
Keywords: Japanese immigrants; Nation; Japanese colonies; Brazil-Maru; Imigrantes japoneses; Nação; Colônias japonesas; Brazil-Maru